Impact of the COVID-19 Pandemic on Clinical Schedules and Physical and Mental Well-Being of Gastroenterology Nonphysician Healthcare Workers: A Nationwide Survey. (July 2021) - Keihanian, Tara; Sharma, Prateek; Sandhu, Dalbir S.; Sussman, Daniel A.; Tabibian, James H.; Girotra, Mohit
Abstract : COVID-19 was declared a pandemic in March 2020 by the World Health Organization. To minimize exposure and because of limited personal protective equipment resources, most gastroenterology practices were curtailed/modified during the surge, with slow reopening to a normal/semi-normal schedule. Gastroenterology healthcare workers have been impacted greatly by COVID-19, resulting in job and wage insecurity. The aim of our study was to understand the impact of COVID-19 on gastroenterology healthcare workers across the United States. A web-based survey, consisting of 40 questions, was disseminated among gastroenterology practices across the United States via en masse e-mails and direct contact by authors. In total, 223 gastroenterology healthcare workers completed the survey; 56.1% were from academic settings. COVID-19 impacted the work schedule of 85.2% of participants, with reduced weekly work hours (38.1%), duty reassignment (22.4%), and furlough (13.9%). Uncertainty about job and/or future wages/benefits after reopening was noted in 41%, which was significantly associated with the presence of physical ( p = .021) and mental/emotional symptoms ( p = .045). Worsening of pre-existing physical and/or mental/emotional conditions was observed in 53%. Inadequate personal protective equipment availability, lack of temporary housing and/or childcare facilities, as well as job insecurity appear to be the important factors leading to worsening physical/mental/emotional conditions among gastroenterology healthcare workers.